Language policy of the European Union - Shpenik Kateryna Maria („RIK-U” Kft., 2018)
Abstract. Language policy is what governments implement through legislation, court decisions or policy to regulate the usage of languages, language cultivation skills that are needed to meet national priorities or to establish the rights of individuals or groups to use and maintain languages. Many scientists, artists, writers, politicians, leaders of linguistic communities, and defenders of linguistic human rights are heavily concerned with the preservation of cultural and linguistic diversity in today’s world. The European Union (EU) is a political and economic union of 28 countries located in Europe. Its foundations lay in the European Coal and Steel Community, established in 1951 by the Treaty of Paris, and the European Economic Community, established in 1957 by the Treaty of Rome. The original members, known as the European Communities or Inner Six were Belgium, France, West Germany, Italy, Luxembourg and the Netherlands. The European Union was formally founded with the Maastricht Treaty, that came into force on November 1, 1993. Since then, the member-states have been cooperating in different fields and working on the equality of rights of every single citizen.
https://kmf.uz.ua/wp-content/uploads/2018/11/Multicult-Diversity_Book-of-Abstracts_23-10-2018.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00006453
Keywords: European Union; language policy